Recent Developments in Mercury Cadmium Telluride IR Detector Technology. (16th September 2015) - Antoszewski, Jarek; Akhavan, Nima Dehdashti; Umana-Membreno, Gilberto; Gu, Renjie; Lei, Wen; Faraone, Lorenzo
Abstract : In spite of many attempts to find better material for infrared detectors, HgCdTe still dominates the high performance end of the market. At present, the research in this field is directed towards high pixel density, high yield, reduced cooling and hyperspectral operation. Long lasting issue of availability of high quality, large area substrates for epitaxial growth of HgCdTe seems to be easing recently with development of 4" CdZnTe lattice matching substrates reported recently. The quality of HgCdTe grown on alternative substrates like silicon, GaAs or recently investigated GaSb still falls behind that achievable on CdZnTe due to large lattice mismatch leading to high defect density. Recent effort to scale down the pixel size and pitch resulted in development of diffraction limited high definition focal plane arrays. Implementation of unipolar n-type/barrier/n-type detector structure in HgCdTe material system has been recently proposed and studied intensively. Due to superior transport and optical properties of HgCdTe it is expected that, when optimized, these structures will allow for background limited performance at significantly higher operating temperatures.